IMPLEMENTATION OF FACE PAINTING AS A STRATEGY TO DEVELOP SELF-CONFIDENCE IN CHILDREN WITH SPECIAL NEEDS IN SPECIAL SCHOOLS - Fie Dzikry, Lataniya (Universitas Islam Balitar, 2024)
Face painting activities have been widely used as an interactive art form that not only provides entertainment, but also has therapeutic potential in developing children's emotional and social skills, especially for children with special needs. This study aims to explore the implementation of face painting as a strategy to increase the self-confidence of children with special needs in Special Schools (SLB). The method used is a qualitative approach with the techniques used, namely observation and interviews. Participants in this study were teachers, students with special needs, and parents at SLB Kemala Trenggalek. The results of the study showed that face painting activities were able to create a pleasant learning atmosphere, strengthen social interactions, and encourage children to be more confident in expressing themselves. In addition, the involvement of children in the process of choosing the design and color of the face painting also increased their sense of autonomy and personal satisfaction. Children with special needs at SLB Kemala Trenggalek showed their self-confidence by forming face painting in a creative way. This study concludes that face painting can be implemented as an alternative strategy for developing the self-confidence of children with special needs in an inclusive school environment. The recommendation for education practitioners is to utilize creative and interactive methods that can be adapted to the needs of individual children. In addition, the recommendation for schools is as an additional learning model for children so that children are more creative and skilled in developing their qualities, then with face painting children can be creative and express emotions and creative abilities within themselves.